House of John F. Andrew at 32 Hereford Street, ca. 1895 - Unknown (Tufts Archival Research Center, 2005)
Street-level view north of 32 Hereford Street, located at the northeast corner of Hereford Street and Commonwealth Avenue. The facade of the house faces west-southwest towards Hereford Street. The southeast elevations of houses along Marlborough Street are visible to the left of the Andrew house. 305 Commonwealth Avenue is located to the east-northeast or to the right of 32 Hereford Street. A street lamp is visible on the northeast corner of Commonwealth Avenue and Hereford Street. Designed by McKim, Mead and White, 1884-89 7 1/4 x 9 3/16 Photographs